Safety and efficacy of paliperidone extended-release in Chinese patients with schizophrenia: a 24-week, open-label extension of a randomized, double-blind, placebo-controlled study - Hongyan Z; Li H; Liu Y; Wu C; Wu Q; Nuamah I; Jianguo S; Shiping X; Gang W; Gopal S (Neuropsychiatric Disease and Treatment)
Hongyan Zhang,1 Huafang Li,2 Yanning Liu,3 Cathy Wu,3 Qingqi Wu,3 Isaac Nuamah,4 Jianguo Shi,5 Shiping Xie,6 Gang Wang,7 Srihari Gopal4 1Peking University 6th Hospital, Peking University Institute of Mental Health, Key Laboratory of Mental Health, Ministry of Health (Peking University), Beijing, 2Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 3Janssen Research & Development, Shanghai, People’s Republic of China; 4Janssen Research & Development, LLC, Titusville, NJ, USA; 5Xian Mental Health Center, Xian, 6Department of Psychiatry, Nanjing Brain Hospital, Nanjing, 7Mood Disorders Center, Beijing Anding Hospital, Beijing, People’s Republic of China Objectives: The long-term safety, tolerability, and efficacy of paliperidone extended-release (ER) were evaluated in Chinese patients with schizophrenia.Methods: Patients (aged ≥18 years) with schizophrenia (Diagnostic and Statistical Manual of Mental Disorders, 4th edition criteria) who had completed run-in (8-week), stabilization (6-week), and double-blind (DB) phases (variable) of a phase-3, placebo-controlled study entered this 24-week, open-label extension (OLE) study. These patients, who had either experienced a relapse or remained relapse-free through DB phase of the study, were treated with flexible-dose paliperidone-ER (3–12 mg/day) during the OLE phase. Major safety evaluations included treatment-emergent adverse events (TEAEs) and extrapyramidal symptoms. Efficacy endpoints included changes in Positive and Negative Syndrome Scale total score, Clinical Global Impression-Severity scale, and Personal and Social Performance scale from OLE baseline to OLE endpoint.Results: Out of 106 patients who entered the OLE phase (placebo: 59, paliperidone-ER: 47), a total of 85 (80%) completed it. Thirty-five (33%) patients experienced at least one TEAE; most common were akathisia, somnolence, nasopharyngitis, and constipation (3.8% each). Serious TEAEs were noted in two patients (completed suicide; schizophrenia worsening). No TEAEs with an onset during the OLE phase led to discontinuation. Extrapyramidal symptoms related-TEAEs were reported in eight (7.5%) patients. Mean (standard deviation) changes in Positive and Negative Syndrome Scale total scores (–10.4 [13.2]), Clinical Global Impression-Severity scores (–0.6 [0.96]) and Personal and Social Performance scores (7.4 [13.2]) from OLE baseline to OLE endpoint showed patients who had been treated with placebo during the DB phase experienced more pronounced improvements.Conclusion: In this OLE study, flexibly dosed paliperidone-ER (3–12 mg/day) was tolerable and efficacious in Chinese patients with schizophrenia. Keywords: CGI-S score, paliperidone, PANSS score, PSP score